Border Governance: Reframing political transition in Myanmar. (March 2022) - McCONNACHIE, KIRSTEN; HO, ELAINE LYNN-EE; KYED, HELENE MARIA
Abstract: Borderlands and bordering processes are central to politics and the governance of people, goods, and territories, not only as markers of territorial-administrative control but also as practices that shape the dynamics of inclusion and exclusion, mobility/immobility, and relations of power and authority. This special issue focuses on Myanmar, where political governance is deeply entangled with ethnicity, territory, borders, and bordering processes. We attempt to untangle these relationships by adopting an approach that combines consideration of how borderlands are governed with recognition of the ways in which borders, borderlands, and border populations shape governance and administration. We define this approach as 'border governance', by which we mean governance in, of, and through borderlands . In this introduction, we explore the meaning and significance of border governance as it relates to Myanmar, its ethnic border states, and their relations to other nations bordering the country. In doing so, we engage with and develop scholarly debates in three primary areas: (i) Borders, territoriality, and bordering processes; (ii) Plural governance and everyday bordering; (iii) Peacebuilding and the borders of transition. The articles in this special issue were written prior to the military coup of February 2021. Nevertheless, the central arguments presented here remain relevant, as does our conclusion: to achieve lasting peace in Myanmar, the borderlands must be at the centre.